Utilization of Tide Observation and Satellite Altimetry Data for Detecting Land Vertical Movement - Maritsa Faridatunnisa (Universitas Gadjah Mada, 2019)
Indonesia is one of the country that often experiences earthquakes and volcanic eruptions because of its position on the meeting point of three active tectonic plates, namely the Eurasian, Indo-Australian and Pacific plates. This causes movement or deformation both horizontally and / or vertically. Current movement monitoring is done using GNSS technology. However, the distribution of monitoring points are not spread evenly and the results of GNSS observation have weaknesses in their vertical components. An alternative method for monitoring movement especially in vertical components is using combination of tide observation and satellite altimetry data. The measurement concept of satellite altimetry produces absolute sea level values and its not affected by plate movements,besides tidal measurements which sensors are installed on the ground so that the sea level values are affected by land uplift or subsidence at that location. This study used main data, namely long-period tidal observation data and GDR (Geophysical Data Record) satellite altimetry. GNSS observation data is needed as a control of vertical movement. The differences in spatial and temporal resolution of tidal observation and satellite altimetry are overcome by two methods, namely the daily and monthly methods. Each of these methods will produce an annual SLR value (Sea Level Rise) from tidal data and satellite altimetry calculated using linear regression. The difference between the tidal and satellite altimetry data trends is compared with the vertical movement value from GNSS data. The results of the study indicate that the determination of vertical movement can be done using tidal observation and satellite altimetry data, especially using the monthly method. The trend of vertical movements of tidal observation and satellite altimetry data shows the same pattern with land vertical movement of GNSS data even though the value is different. Therefore, the method to determine vertical movement from hydrological data can be used as an initial observation on a coastal area regarding the phenomenon of vertical movements that occur in the area.